Establishment of a core outcome set for burn care research: development and international consensus. Issue 1 (8th July 2022) - Young, Amber; Davies, Anna; Tsang, Carmen; Kirkham, Jamie; Potokar, Tom; Gibran, Nicole; Tyack, Zephanie; Meirte, Jill; Harada, Teruichi; Dheansa, Baljit; Dumville, Jo; Metcalfe, Chris; et al.
Abstract : Objective: To develop a core outcome set for international burn research. Design: Development and international consensus, from April 2017 to November 2019. Methods: Candidate outcomes were identified from systematic reviews and stakeholder interviews. Through a Delphi survey, international clinicians, researchers, and UK patients prioritised outcomes. Anonymised feedback aimed to achieve consensus. Pre-defined criteria for retaining outcomes were agreed. A consensus meeting with voting was held to finalise the core outcome set. Results: Data source examination identified 1021 unique outcomes grouped into 88 candidate outcomes. Stakeholders in round 1 of the survey, included 668 health professionals from 77 countries (18% from low or low middle income countries) and 126 UK patients or carers. After round 1, one outcome was discarded, and 13 new outcomes added. After round 2, 69 items were discarded, leaving 31 outcomes for the consensus meeting. Outcome merging and voting, in two rounds, with prespecified thresholds agreed seven core outcomes: death, specified complications, ability to do daily tasks, wound healing, neuropathic pain and itch, psychological wellbeing, and return to school or work. Conclusions: This core outcome set caters for global burn research, and future trials are recommended to include measures of these outcomes.